RANCANG BANGUN GAME EDUKASI PEMBELAJARAN ANAK USIA DINI PADA RA MIFTAHUL FATAH SAYUTAN BERBASIS ANDROID - Emi Wulandari; Ghulam Asrofi Buntoro; Arin Yuli Astuti (KOMPUTEK, 2020)
Along with the development of technology that is so sophisticated and has a huge impact on human life, we cannot help but be required to keep up with the times. Especially for early childhood Smartphones are very influential on the development of their brains because their memory is so sharp and easy to hone. Usually children between the ages of 4 -6 years really easily perceive what they see because their capacity for thinking or memory is still very high to catch something new. Therefore the authors plan to make educational games for children RA miftahul fatah sayutan based on android to provide learning that is just learning while playing, with the hope of providing an educational stimulus so that children are not bored and bored with what their teacher has taught. . Educational games are learning applications for early childhood from 4 - 6 years old which contain some of the features of the 1st and 2nd semester magazines. The method and development of this educational application uses the waterfall method. By implementing this game application it is hoped that it can help the learning process of early childhood in gaining insight into the mindset, creativity and knowledge that is smarter.